Rancang Bangun Hot Plate Magnetic Stirrer Berbasis Mikrokontroler - budi darmawan; Suthami Ariessaputra; Muhammad Alfarizi Putra (DIELEKTRIKA, 2023)
Chemical laboratories require additional equipment that is used as a mixer into the solution or chemical to be studied. The mechanism that is often used to accelerate the process of dissolving or mixing chemicals is heating and stirring. In addition to dissolving faster, the resulting solution will also be more homogeneous. In this research a Hot Plate Magnetic Stirrer was designed and manufactured by setting the time, temperature and stirring speed via a keypad so that accurate time, temperature and speed were obtained. The Hot Plate Magnetic Stirrer made in this study uses an infrared sensor to detect the speed of stirring, and an NTC 3950 sensor which is immersed in the solution to detect the temperature of the solution during stirring. The Hot Plate Magnetic Stirrer tool that has been made can run as expected. In the stirring time test, the system will work according to the input time. In testing the stirring temperature the system can maintain the stability of the solution temperature as desired with a maximum temperature of 110˚C. In the stirring speed test, the maximum speed of stirring was obtained, namely 1500 RPM when stirring using a beaker glass with a diameter of 6 cm and a bar magnet length of 4 cm.